2019
DOI: 10.1038/s41598-019-49420-6
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale analysis of hydrogen-induced softening in f.c.c. nickel single crystals oriented for multiple-slips: elastic screening effect

Abstract: Hydrogen-deformation interactions and their role in plasticity are well accepted as key features in understanding hydrogen embrittlement. In order to understand the nature of the hydrogen-induced softening process in f.c.c. metals, a substantial effort was made in this study to determine the effect of hydrogen on the tensile stress-strain behavior of nickel single crystal oriented for multiple-slips. It was clearly established that the hydrogen softening process was the result of a shielding of the elastic int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 48 publications
0
11
0
1
Order By: Relevance
“…Even though the local strain of the region close to the fracture surface is expected to be higher than the other areas, the misorientation of LEDS just beneath the quasi-cleavage surface is almost the same as that of the uncharged specimen. The effects of hydrogen on LEDS formation were extensibly studied in nickelbase metals and alloys [42][43][44][45][46] . Their results indicated that LEDS size was smaller under the presence of hydrogen in face-centered cubic (FCC) structures.…”
Section: Sem Observation Resultsmentioning
confidence: 99%
“…Even though the local strain of the region close to the fracture surface is expected to be higher than the other areas, the misorientation of LEDS just beneath the quasi-cleavage surface is almost the same as that of the uncharged specimen. The effects of hydrogen on LEDS formation were extensibly studied in nickelbase metals and alloys [42][43][44][45][46] . Their results indicated that LEDS size was smaller under the presence of hydrogen in face-centered cubic (FCC) structures.…”
Section: Sem Observation Resultsmentioning
confidence: 99%
“…It is clear that hydrogen can introduce 2 different softening and hardening effects on nickel single crystal depending on the plastic strain and the strain rate. When a metal is tensile strained, the presence of hydrogen induces a hardening at low deformation (shear strain < 0.1 ), which is mainly due to hydrogen in the Cottrell atmosphere increasing the drag stress of dislocations [26,27], an effect that is also observed in polycrystalline nickel [28,29]. A softening effect is observed when a metal is oriented for single and multi-slips at a higher plastic strain in the presence of hydrogen [26,27].…”
Section: Introductionmentioning
confidence: 94%
“…The effect of hydrogen on the mechanical response of strained (tensile) nickel single crystal oriented for single slip [23][24][25][26] and multiple slips [23,27] has been studied. It is clear that hydrogen can introduce 2 different softening and hardening effects on nickel single crystal depending on the plastic strain and the strain rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entretanto, agora cabe mencionar sua relação com a velocidade das discordâncias e da migração do soluto.De acordo comWang et al (2017), há um limite natural de velocidade de movimentação das discordâncias em que a blindagem pode operar devido à necessidade de formar atmosferas sem que o atrito com a rede seja aumentado. Por sua vez,Ghermaoui et al (2019) destacaram que a blindagem ocorre quando a mobilidade do hidrogênio é maior que a mobilidade das discordâncias, enquanto que o endurecimento prevalece quando a mobilidade do hidrogênio é similar ou menor que a mobilidade das discordâncias gerando arrasto. Desta maneira, a blindagem se manifesta apenas para faixas limitadas de concentração de H, temperatura e velocidade de difusão do H, e fora dessas faixas é substituído pelo efeito oposto, ou seja, ocorrerá endurecimento(PETUKHOV, 2007).SegundoMorasch e Bahr (2001), essa mudança no mecanismo de deformação explicaria muitos dos resultados conflitantes na literatura sobre o comportamento das discordâncias na presença de hidrogênio.…”
unclassified